2021
DOI: 10.3390/ijerph18073837
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m Gonna Tell You about How Mrs Rona Has Affected Me’. Exploring Young People’s Experiences of the COVID-19 Pandemic in North East England: A Qualitative Diary-Based Study

Abstract: Children and young people risk being ‘disproportionately harmed’ by the COVID-19 pandemic. Whilst an evolving body of literature focuses on the impact of the pandemic on the mental health and wellbeing of children and young people, less attention has been paid to the collection of qualitative, exploratory data. The aim of this study was to examine young people in North East England’s experiences of COVID-19 and associated control measures. Flexible, qualitative diaries were collected with 31 young people aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 49 publications
8
58
0
Order By: Relevance
“…As such, online conversations about COVID-19 and mental health show the messy and entangled nature of causality and illustrate the multiple and cumulative causes of anxiety, depression, suicidal thoughts and self-harm. This finding aligns with Scott, McGowen and Visram [ 39 ] diary-based study in which young people spoke about the differing impacts that lockdowns and school closures were having on their mental health. As such, our findings demonstrate that young people’s mental health through the pandemic has been profoundly shaped by their social contexts and societal belonging.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As such, online conversations about COVID-19 and mental health show the messy and entangled nature of causality and illustrate the multiple and cumulative causes of anxiety, depression, suicidal thoughts and self-harm. This finding aligns with Scott, McGowen and Visram [ 39 ] diary-based study in which young people spoke about the differing impacts that lockdowns and school closures were having on their mental health. As such, our findings demonstrate that young people’s mental health through the pandemic has been profoundly shaped by their social contexts and societal belonging.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is also crucial to recognise that there have been continual conversations amongst young people on social media about how being away from school improved their mental health and wellbeing, with descriptions of “anxiety returning” when schools and universities reopened. As Scott, McGowan and Visram [ 39 ] have also suggested, “it may be that schools are not the panacea to social ills”. COVID-19 has highlighted the different experiences that young people have at school, it being both a space of socialisation and safety, but also one of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al also found young people reported feeling less confident and like an ‘imposter’ following cancelled examinations due to the pandemic. 38 Teaching staff may be well-placed to address these concerns by clearly communicating revised assessment plans and providing reassurance about the assessment process for future students affected by pandemic-related education disruptions. Teachers also require clear guidance and coordination from government and educational authorities to be able to deliver these messages, 34 which were reported to be absent during the first wave of educational establishment closures.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings relating to the added stress and worry for young people due to disruption to everyday life and to education are similar to themes found in other qualitative work exploring the experiences of young people during the pandemic. 7 , 8…”
Section: Discussionmentioning
confidence: 99%